(untitled) (Mugda Medical College Journal, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a global health concern. Around 56% of subjects in Bangladesh go undiagnosed, increasing the risk of stroke and cardiovascular issues. Iron stores’ impact on diabetes is gaining attention, with ferritin as a key biomarker. Hyperferritinemia probably contributes to insulin resistance and subsequently to decreased insulin secretion, causing the development of insulin resistance. The link between ferritin and insulin resistance (IR) varies based on ethnicity, gender, and glycemic state. Objectives: This study investigates serum ferritin levels in different glycemic stages and explores potential correlations between ferritin and insulin resistance markers (blood glucose, serum insulin, and HOMA-IR) Methods: The study was conducted at the Department of Biochemistry, Sir Salimullah Medical College, Dhaka, Bangladesh, from March 2018 to February 2019. A total of 140 subjects were included to conduct this study. Participants were categorized into three groups: those with normal fasting glucose (NFG group), impaired fasting glucose (IFG group), and newly diagnosed type 2 diabetes mellitus (Diabetic group) according to WHO (2006) criteria. A purposive convenient sampling method was used, focusing on adults aged 25 to 55 years. Exclusion criteria were applied to eliminate individuals with inflammatory diseases, chronic conditions, major cardiovascular events, anemia, or specific medications that could affect ferritin levels. Results: The study found that serum ferritin levels significantly differed among three glycemic groups (NFG, IFG, and T2DM) with higher levels in T2DM. IFG and T2DM groups also had elevated serum insulin and HOMA-IR. Serum ferritin correlated strongly with fasting blood glucose, serum insulin, HOMA-IR, and BMI. The highest tertile of ferritin levels were associated with the IFG & diabetic group. Conclusion. Elevated serum ferritin levels in IFG and type 2 diabetes may significantly impact glucose regulation. Compared to NFG, there are high insulin resistance markers (fasting insulin, glucose, HOMA-IR) in T2DM and IFG. They have crucial implications for both therapy and prognosis in these conditions. Mugda Med Coll J. 2023; 6(2): 57-63